Hubungan Peran Keluarga Dengan Perilaku Penyalahgunaan Narkoba Pada Remaja di Kabupaten Sidenreng Rappang - Pannyiwi, Rahmat; Ali, Akhwan; Yulis, Dian Meiliani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Drug abuse among adolescents is a growing public health problem, particularly in Sidenreng Rappang (Sidrap) Regency. The family, as the closest environment for adolescents, plays a crucial role in preventing risky behavior. This study aims to determine the relationship between family roles and drug abuse behavior among adolescents in Sidrap Regency. The research design used a cross-sectional study with a quantitative approach. The sample consisted of 120 adolescents aged 15–24 years, selected using a purposive sampling technique. The research instrument was a structured questionnaire regarding family roles (communication, supervision, emotional support, and religious values) and drug abuse behavior. Data analysis used the chi-square test. The results showed a significant relationship between family roles and drug abuse behavior (p < 0.05). Adolescents from families with poor communication, low supervision, and minimal emotional support are at higher risk of drug abuse. This study emphasizes the importance of strengthening the family's role in preventing drug abuse among adolescents.